2016
DOI: 10.3346/jkms.2016.31.5.674
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception about Clinical Research Shapes Behavior: Face to Face Survey in Korean General Public

Abstract: Considering general public as potential patients, identifying factors that hinder public participation poses great importance, especially in a research environment where demands for clinical trial participants outpace the supply. Hence, the aim of this study was to evaluate knowledge and perception about clinical research in general public. A total of 400 Seoul residents with no previous experience of clinical trial participation were selected, as representative of population in Seoul in terms of age and sex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 19 publications
4
28
1
2
Order By: Relevance
“…The current results are supported by similar findings in studies conducted in healthcare settings (with patients and/or their families) within the KSA 17–20. The reason may be the lack of institutional and national campaigns promoting CTs 5 25…”
Section: Discussionsupporting
confidence: 88%
“…The current results are supported by similar findings in studies conducted in healthcare settings (with patients and/or their families) within the KSA 17–20. The reason may be the lack of institutional and national campaigns promoting CTs 5 25…”
Section: Discussionsupporting
confidence: 88%
“…A Saudi Arabian questionnaire study also reported this (AL‐Tannir et al, ). All three studies have several limitations regarding their generalisability to our findings, including choice of quantitative research method and the fact that the participants were not necessarily cancer patients or had not necessarily been offered trial participation (AL‐Tannir et al, ; Burt et al, ; Choi et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Also, a questionnaire study concluded that altruism was the most influential factor for the Indian population (Burt et al, ). Both studies reported that the populations had a substantial distrust towards clinical trials (Burt et al, ; Choi et al, ). A Saudi Arabian questionnaire study also reported this (AL‐Tannir et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors argued that perceiving a trial as meaningful may, in fact, be associated with previous knowledge, and not information obtained just before the trial. The authors of the above-cited study also placed great importance on the Internet and media as carriers of such information as the majority of research participants searched for information on the Internet [19]. In terms of informed consent, recently a trend has been observed of posting ICFs on-line as a method of acquainting the future research participants with the trial, and simultaneously facilitating the decision-making process.…”
Section: Quality Of Informed Consent As a Challenge Of The 21st Centrymentioning
confidence: 99%